The Juridical Review on Payment Security and Protection of Authors' Rights in Journal Publication - Adnan, Muhammad Ali; Sunarto, Atika; Khair, Azizan (JURNAL AKTA, 2025)
Copyright is an exclusive right held by the creator over his/her work, whether in the form of scientific, literary, artistic, or technological works. In the context of publishing scientific journals, copyright relates to control over published scientific works, including distribution, reproduction, and royalty payments. Meanwhile, royalties are payments received by authors or creators in return for the use of their creative works, which are usually calculated based on the number of copies or accesses made to the work. The main objective of this study is to Legal Review of Payment Security and Protection of Authors' Rights in Journal Publication. The method used is a qualitative approach with an analysis of scientific journal publishing contracts and interviews with authors involved in the publication. The results of the study indicate significant inequality between publishers and authors in terms of the distribution of copyright and royalties. Many authors, especially in developing countries, do not receive fair compensation, even though their work provides great benefits to publishers. The practice of transferring copyright entirely to publishers and the lack of transparency in royalty reports are major factors that exacerbate this injustice. The conclusion of this study is that stricter and more transparent regulations are needed to ensure a fair distribution of royalties, as well as protection of authors' copyright. Open access models and merit-based payment systems are considered potential solutions to create a fairer ecosystem in scientific journal publishing. Authors are encouraged to gain more control over their work, while publishers need to provide transparent reporting on the use of the work and the distribution of royalties.